EFFECT OF 2 YEARS OF THE COVID-19 PANDEMIC ON ANTHROPOMETRIC, HEMODYNAMIC AND FUNCTIONAL VARIABLES OF ELDERLY LOW-INCOME WOMEN - Fernandes, Bianca [UNESP]; do Amaral, Vanessa Teixeira [UNESP]; Campanha, Luana Marcela Ferreira [UNESP]; Cheretti, Vitória Lini [UNESP]; Ciolac, Emmanuel Gomes [UNESP] (Elsevier, 2024)
Background The COVID-19 pandemic (respiratory infection caused by the new severe acute respiratory syndrome coronavirus 2 “SARS-CoV-2”) may have been responsible for the worsening of health indices (such as anthropometric, hemodynamic, and functional), including in the elderly population. Elderly individuals who previously participated in regular physical exercise programs and had their activities interrupted may lose or reduce the benefits acquired by exercise. Objectives To investigate the behavior of anthropometric, hemodynamic, and functional variables of previously active low-income elderly women during the first two years of the COVID-19 pandemic. Methods 56 low-income elderly women (73.01 ± 5.4 years) who discontinued their participation in community physical exercise programs (high-intensity interval training + resistance training; moderate-intensity continuous training + resistance training; and isolated resistance) due to pandemic containment measures, had body mass, body mass index (BMI), waist circumference (WC), blood pressure (BP), heart rate (HR), arterial stiffness, flexibility (sit and reach test), handgrip strength (hydraulic wrist dynamometer), lower limb strength (five-time sit to stand test, FTSTS), agility and balance (Timed Up and Go, TUG) and aerobic performance (6-minute walk test, 6MWT) evaluated before and after two years of the pandemic. All ethical procedures required for research were followed. Results There was a reduction in body mass (-1.3 kg, P = 0.046), BMI (-0.6 kg/m², P = 0.002) and HR (-4.3 bpm, P = 0.004); increased WC (2.6 cm, P = 0.007), systolic BP (6.9 mmHg, P = 0.018) and arterial stiffness (1.24 m/s, P < 0.001); and worse performance on the sit and reach test (-1.8 cm, P < 0.001), strength and handgrip (-1.1 kgf, P = 0.009) and FTSTS (1.0 s, P = 0.003 ) and 6MWT (-74.2 m, P < 0.001) over two years of follow-up. Conclusion The first two years of the COVID-19 pandemic were detrimental to the health of previously active elderly women, specifically in terms of WC, systolic BP, arterial stiffness, and functional capacity (flexibility and hand and lower limb grip strength). The worst decline found was in the 6MWT, which demonstrates a relevant worsening of walking (and cardiorespiratory) capacity in this population. Despite this, there were no significant changes in other study variables, which suggests that previously active elderly women may have less deleterious effect of aging even in longer periods of drastic changes in habits and routine, as an example, the COVID-19 pandemic. Implications The present study suggests the importance for elderly women to remain physically active and the urgent return of regular physical exercise to maintain (or decrease the loss/worsening) of cardiovascular health and functional capacity of low-income elderly women.